#60: Attention Deficit Hyperactive Disorder and Oppositional Defiant Disorder in Adolescents Living with HIV/AIDS - A Cross Sectional Study. (28th June 2021) - Bhat, Kamalakshi G; Nalwalla, Zahabiya; Joseph, Nitin
Abstract: Introduction: Perinatally HIV infected neonates are surviving into adulthood with an impact on mental and emotional health. Attention deficit hyperactive disorder (ADHD) and Oppositional Defiant disorder (ODD) are few of the common behavioral disorders, which have been found to have a higher prevalence amongst HIV infected children. Objectives: The objectives were to assess the proportion of ADHD and ODD in adolescents living with HIV/AIDS and to find its association with various factors. Materials and Methods: 88 adolescents aged 10–19 years living with HIV/AIDS were included in the study. The Swanson, Nolan Pelham (SNAP-IV) scale was administered to the caretakers and children were assessed for the proportion of ADHD/ODD. Association between those who scored positive with duration of treatment, CD4 counts, stage of disease and socio-demographic variables were done using statistical tests. Results: Our study included 88 participants, of whom 9 scored positive in the inattention subset resulting in a proportion of 10.2%. 5 participants had symptoms of hyperactivity/impulsivity resulting in a proportion of 5.6% and 1 had combined symptoms with a proportion of 1.1%. 13 scored positive in the opposition/defiant subset resulting in a proportion of 14.7%. No statistical significance was found between duration of treatment, CD4 count, stage of disease, socio-demographic variables and ADHD/ODD. Conclusion: The proportion of ADHD and ODD in this study was found to be comparable to the general population. A holistic approach to improve the long-term health of these youth is needed to ensure that our success in achieving survival of HIV-infected children from infancy is maintained into adulthood.